Necessary skills for the collection of field information and application of a measurement instrument in an investigation - Caicedo, Johans Steven
Apprentices from the research hotbed - CGTS SENA integrated management systems during their field work phase detected situations and training deficiencies of the personnel that applied a research instrument, when reviewing the bibliography they denote how the research is not only necessary for the institution in its grow academically, as requested by SACES for the granting of the Qualified Registry, but very important in the professional growth of the graduate, and that is when the task of establishing what or which should be the minimum competencies that an apprentice must have in order to to have sufficient bases and guidelines for their professional development as a graduate, the above is done by applying the SENA teaching-learning model, but also includes recognition and application in the context of today’s apprentice.